Mathematical Communication in Mathematics Education: Productivity, Impact, and Emerging Themes from a Bibliometric Perspective - Yuni Arrifadah; Mega Suliani (EDUPEDIA PUBLISHER, 2026)
Purpose: Mathematical communication is a key competence in mathematics education that supports students’ reasoning, conceptual understanding, and problem solving. Despite the growing volume of empirical studies, a systematic overview of research trends and scholarly influence in this field remains limited. Methodology: This study aims to map the research landscape of mathematical communication in mathematics education through a bibliometric analysis. A total of 141 English-language journal articles published between 2015 and 2025 were retrieved from the Scopus database and selected following PRISMA guidelines. Bibliometric techniques—including publication and citation analysis, country and institutional performance analysis, and keyword co-occurrence analysis—were conducted using VOSviewer. Findings: The results show a steady increase in research output, particularly after 2019, with Indonesia emerging as the most productive country in terms of publication count. Significance: Research themes are predominantly centered on instructional strategies, student learning outcomes, problem solving, and mathematical literacy. These findings provide conceptual insights into the evolution of mathematical communication research and inform future theoretical and methodological developments in mathematics education.